ANALISIS KEUNTUNGAN DAN PROFITABILITAS USAHATANI RUMPUT LAUT DI KECAMATAN JEROWARU KABUPATEN LOMBOK TIMUR - Widiyanti, Ni Made Nike Zeamita; Nursan, Muhammad; Yusuf, M; Husni, Syarif; FR, Aeko Fria Utama; Fadli, Fadli (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2023)
Improving community livelihoods can be done through employment in the marine and fisheries sector. One of the strategic commodities to be developed is seaweed. Seaweed is widely used as a processed ingredient for food, cosmetics, and medicine. East Lombok Regency is one of the largest seaweed development areas in West Nusa Tenggara, even one of its areas is called Seaweed Village. The method of determining the location using purposive sampling and the method of determining the sample with incidental sampling. This study aims to determine the benefits and profitability of seaweed farming in Jerowaru District, East Lombok Regency. Based on the results of the study, the average profit obtained was Rp 55,283,003 per long line per year, where the average total revenue was Rp 65,630,000 per long line per year and the average total cost was Rp 10,676,582 per long line per year. Then the profitability analysis is calculated with NPM (Net Profit Margin) and ROI (Return Of Invesment), where the NPM value is 534.29% and the ROI value is 83.23%, meaning that seaweed farming is feasible. Keywords: Profit, Profitability, Seaweed